Marker-trait association study for root-related traits in chickpea (Cicer arietinum L.) - Zahra SHEKARI; Zahra TAHMASEBI; Homayoun KANOUNI; Ali ashraf MEHRABI (Acta Agriculturae Slovenica)
Root structure modification can improve important agronomic traits including yield, drought tolerance and nutrient deficiency resistance. The aim of the present study was to investigate the diversity of root traits and to find simple sequence repeat (SSR) markers linked to root traits in chickpea (Cicer arietinum L.). This research was performed using 39 diverse accessions of chickpea. The results showed that there is significant variation in root traits among chickpea genotypes. A total of 26 alleles were detected 26 polymorphic bands were produced by 10 SSR markers in the eight linkage groups (LG). The results indicated that there is substantial variability present in chickpea germplasm for root traits. By analyzing the population structure, four subpopulations were identified. PsAS2, AF016458, 16549 and 19075 SSR markers on LG1, LG3, LG2 and LG1 linkage group respectively were associated with root traits. The research findings provide valuable information for improving root traits for chickpea breeders.